STRATEGI PEMASARAN USAHA HOME INDUSTRY IKAN ASIN DALAM PENINGKATAN EKONOMI KELUARGA MASYARAKAT KELURAHAN MALABERO KOTA BENGKULU - Yuliani, Indah; Herfianti, Meiffa (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2024)
The aim of this research is to analyze the marketing strategy of the salted fish home industry business in improving the family economy of the people of Malabero Village, Bengkulu City. This type of research is a qualitative approach. The location of the research conducted by researchers is located in Malabero Village, Bengkulu City,. Data collection techniques in this research are observation, interviews and documentation. The sample in this research was 17 people in the salted fish home industry business, Malabero Village, Bengkulu City. Based on the research results, it was found that in the product sector, 17 salted fish sellers varied their products by varying the types of fish available, then the salted fish sellers created product characteristics. The price sector is where salted fish sellers are able to compete with other entrepreneurs by selling salted fish at prices according to existing standards or markets. The distribution sector is where salted fish sellers have carried out distribution well and in a planned manner because the distribution reach of selling salted fish is not only within the city but has reached outside the city. In the promotion sector, salted fish sellers already have attractive promotional activities for consumers. Apart from carrying out promotions through verbal communication for people they know, salted fish sellers have also promoted their salted fish through social media, namely Facebook, Tik Tok and WA which can help in the process. promotion. By implementing strategies in the product, price, distribution and promotion sectors, entrepreneurs will increase income thereby improving community welfare.  Keywords: Strategy, Home Industry, Marketing, Economic Improvement